2020
DOI: 10.1088/2053-1591/ab66a0
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of zero valent iron and photocatalytic application for the degradation of dyes

Abstract: In the present investigation, Zero valent iron (ZVI) was synthesized using ferrous sulfate and borohydrate in the presence of EDTA and characterized by x-ray Diffraction (XRD), Energydispersive x-ray (EDX) and Scanning electron microscope (SEM) techniques. The prepared ZVI catalytic activity was evaluated by degrading Acid Red 1 (AR1) and Acid Green 25 (AG25) dyes. The process variables such as pH, initial dye concentration, ZVI dose, contact time, hydrogen peroxide (H 2 O 2 ) and temperature were optimized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…In fact, the Fenton process initiates with the generation of hydroxyl radicals. As a result, Fe O 2] ratio [22,23]. It was indicated the maximum degradation for pigment solution was 93.2% (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In fact, the Fenton process initiates with the generation of hydroxyl radicals. As a result, Fe O 2] ratio [22,23]. It was indicated the maximum degradation for pigment solution was 93.2% (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…15 , the detailed mechanism of AG-25 degradation is shown for the first time, up to the best knowledge of the authors. The degradation mechanism of AG-25 presented in literature is based on the formation of OH radicals by Fenton reaction that induces Ag-25 mineralization, without analysis of the degradation routes and secondary products 60 , 61 . Degradation paths of similar molecules, such as Acid Green 1 62 or Malachite Green 63 , were proposed.…”
Section: Resultsmentioning
confidence: 99%
“…The reductions in COD, TOC and BOD values after treatment of textile real wastewater revealed that immobilized ZnO over PUF is efficient to treat the wastewater containing textile dyes, which are otherwise difficult to treat. Under the current scenario of environmental pollution [6,[14][15][16][57][58][59][60][61][62], there is need to develop and utilize efficient materials that are active under solar light and ZnO/PUF proved to be highly efficient since the activity was considerable under solar light that could possibly be used for the degradation of dyes in textile wastewater [63][64][65][66][67].…”
Section: Photocalytic Degradation Of Dyementioning
confidence: 99%